Analisis Unsur Intrinsik Puisi “Aku Ingin” Karya Sapardi Djoko Damono - Namang, Katharina Woli; Tiara Oktaviani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Literary works and poetry have distinctive characteristics in form, language style, and depth of meaning. Literary works include various forms such AS prose, drama, and poetry. The goal is often to describe the conditions of life, social values, character Psychology, and Inspire readers emotions and thoughts. Literary works provide reflection on the human experience and presenting deep interpretation of the surrounding world. This Research uses a qualitative descriptive method. The aim of this study was to analyze intrinsik Elements of Sapardi Djoko Domono's poetry, which then thoroughly describe these 7 Elements, from this study result there are several intrinsic Elements including, 1) Analyze the theme of poetry, 2). Diction, 3). Tone, 4). Imageryi, 5). Language style, 6). Typography). The results of an analyze of intrinsic Elements of poetry that researchers have carried out is a meaning container in the poetry